An approach to histology-based diagnosis and treatment of Madura foot - Sanjay Singh Chufal; Naveen Chandra Thapliyal; Manoj Kumar Gupta (Journal of Infection in Developing Countries)
Madura foot is a deep mycosis commonly seen in tropical and subtropical countries such as India. Its incidence is likely to rise in temperate regions as well, due to the increase in worldwide travel.